Investigation of some surface properties and thermogravimetric analysis of veneer sheets treated with fire retardants - Aydin Demir; Ismail Aydin (Maderas: Ciencia y Tecnología, 2019)
This study investigated the effects of different fire retardant chemicals on surface and thermal properties of veneer sheets. Beech (Fagus orientalis), alder (Alnus glutinosa), poplar (Populus deltoides) and scots pine (Pinus sylvestris) were chosen as wood species and zinc borate, borax, monoammonium phosphate and ammonium sulfate were chosen as fire retardant chemicals. The samples were impregnated by using the immersion method. Some surface properties such as colour measurements and surface roughness of the veneer sheets were conducted according to CIE L*a*b* system, DIN 4768 standard, respectively. Some thermal properties such as thermal conductivity of the veneer sheets were conducted according to ASTM C 518 & ISO 8301 and weight loss after combustion was determined by thermogravimetric analysis (TGA). According to the results from the study, it was found that fire retardant chemicals increased the thermal conductivity and surface roughness of veneer sheets. Also, TGA experiments showed that all of the fire retardant chemicals decreased the loss in weights.